Kuparivaara - Puolakkavaara - Jouttiaapa.: Beispiele gegenwärtiger Agrarkolonisation in Nordfinnland - Ehlers, Eckart (ERDKUNDE, 1967)
The article attempts, with the example of three settlement areas, to demonstrate the motivation and methods of modern agricultural colonisation in North Finland. Proceeding from the assumption that the physiognomy and economic structure of the colonised areas is strongly influenced by marked local changes in relief, vegetation types and conditions of micro-climate, the development of settlement, current appearance and economic structure of the three areas is described. Comparison of contemporary new settlement with colonised areas from earlier phases of settlement shows that they are different not only in farm size but also in farm stead shape, house-types and farm building form, as well as in the general layout of settlement. In addition, today's new settlements often display differences between themselves. Above all, they divide up according to the varying state of development works and can be regarded as the result of the different social origins of settlers. The colonisation of North Finland, which has been progressing continuously since the beginning of this century, has left clear traces of different phases of settlement in the cultural landscape, through farm sizes, farmstead and house types. Following the re-orientation of Finnish settlement policies, the new farms established under the Land Use Act 1959 represent the most recent phase in the colonisation of North Finland. In future, structural improvement and consolidation of old and small enterprises will take precedence over the establishment of new holdings on State land.